2017
DOI: 10.14569/ijacsa.2017.080411
|View full text |Cite
|
Sign up to set email alerts
|

Using Weighted Bipartite Graph for Android Malware Classification

Abstract: Abstract-The complexity and the number of mobile malware are increasing continually as the usage of smartphones continue to rise. The popularity of Android has increased the number of malware that target Android-based smartphones. Developing efficient and effective approaches for Android malware classification is emerging as a new challenge. This paper introduces an effective Android malware classifier based on the weighted bipartite graph. This classifier includes two phases: in the first phase, the permissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Work done by Altaher classified android malware based on weighted bipartite graph [1]. He used API and permission for the classification but the dataset used for the experiment only limited to 500 dataset.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Work done by Altaher classified android malware based on weighted bipartite graph [1]. He used API and permission for the classification but the dataset used for the experiment only limited to 500 dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, McAffee has also reported that 37 million of malwares have been detected in apps stores in year 2016. 1 Apart from SMS, call log, audio and picture exploitation, Global Positioning System (GPS) has been used by many attackers to exploit smartphones. Through GPS, attackers know the victims" details such as satellite information and every movement can be monitored by them.…”
Section: Introductionmentioning
confidence: 99%